2017
DOI: 10.1590/1806-90882017000200014
|View full text |Cite
|
Sign up to set email alerts
|

NITROGEN SOURCES AND DOSES ON GROWTH AND QUALITY OF SEEDLINGS OF Cassia grandis AND Peltophorum dubium 1

Abstract: -The demand for seedlings of Brazilian native tree species has increased due to the growing number of recovery projects for degraded areas. In order to obtain success in the revegetation, high quality seedlings should be used. Among the factors that affect the quality of seedlings there is nitrogen fertilization, since nitrogen (N) is one of the nutrients required in the largest amount by plants. Thus, this study aimed to evaluate the response of Cassia grandis and Peltophorum dubium seedlings to N sources and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
2
5
0
5
Order By: Relevance
“…In general, our results showed that limestone and N fertilizer application have a positive effect on most of the growth and quality traits of Peltophorum dubium seedlings, and when Peltophorum dubium seedlings are produced in a substrate consisting of a Cerrado sandy soil, the limestone application and use of 200 mg N dm -3 in topdressing should be recommended to obtain high-quality seedlings. These results confirmed those reported by Soares et al (2017), who applied rates ranging from 0 to 200 mg N dm -3 from different sources of N fertilizer, and showed that the optimum N fertilizer rate for the production of Peltophorum dubium seedlings grown in clay soil was 185 mg N dm -3 .…”
Section: Effect Of Nitrogen Fertilizer Rates On the Production Of Pel...supporting
confidence: 90%
See 1 more Smart Citation
“…In general, our results showed that limestone and N fertilizer application have a positive effect on most of the growth and quality traits of Peltophorum dubium seedlings, and when Peltophorum dubium seedlings are produced in a substrate consisting of a Cerrado sandy soil, the limestone application and use of 200 mg N dm -3 in topdressing should be recommended to obtain high-quality seedlings. These results confirmed those reported by Soares et al (2017), who applied rates ranging from 0 to 200 mg N dm -3 from different sources of N fertilizer, and showed that the optimum N fertilizer rate for the production of Peltophorum dubium seedlings grown in clay soil was 185 mg N dm -3 .…”
Section: Effect Of Nitrogen Fertilizer Rates On the Production Of Pel...supporting
confidence: 90%
“…The increase in seedling growth with the application of N fertilizer was expected, since this nutrient plays a fundamental role in physiologic metabolism, being part of several plant molecules and structures (Taiz et al, 2017). Positive responses of N fertilization on the production of Peltophorum dubium seedlings were reported by Cruz et al (2012), Souza et al (2013), andSoares et al (2017). Therefore, it is evident that the N fertilizer application provides higher quality Peltophorum dubium seedlings, being necessary N fertilizations when the demand of the plant is greater than the supply by the substrate.…”
Section: Effect Of Nitrogen Fertilizer Rates On the Production Of Pel...mentioning
confidence: 85%
“…Diversos trabalhos com espécies arbóreas corroboram com o resultado obtido nesse estudo, em que a fertilização nitrogenada influenciou de forma positiva o crescimento inicial e a qualidade das mudas de espécies florestais nativas (Cruz et al 2006, Gonçalves et al 2008, Marques et al 2009, Tucci et al 2009, Gonçalves et al 2010, Feitosa et al 2011, Cruz et al 2011, Caione et al 2012, Ciriello et al 2014, Mews et al 2015, Goulart et al 2016, Carvalho et al 2016, Soares et al 2017. O nitrogênio faz parte de vários compostos nas plantas, como aminoácidos, ácidos nucléicos e clorofila (Cantarella 2007), o que justifica sua absorção em maiores concentrações pelas plantas.…”
Section: Discussionunclassified
“…An increase in N resulted in a a reduction in the dry mass of the cuttings. This occurred because increasing N promotes vegetative growth and stem elongation (CIRIELLO, GUERRINI & BACKES, 2014;SOARES et al, 2017), i.e., the greater availability of N may have resulted in thinner or less dense stems that were therefore lighter due to the competition for resources, such as solar radiation, caused by the higher number of secondary stems and cuttings and greater fresh mass of the stems (data not shown).…”
Section: Dry Mass and Macronutrient Content Of The Clonal Cuttingsmentioning
confidence: 99%